Influence of ‘Mann Ki Baat’ on Farmers Producer Organizations (FPOs): Lessons from Successful Cases - V. Venkatasubramanian,; B. T. Rayudu,; K.Thimmappa,; Mallikarjun B. Hanji,; J. P. Mishra,; G. Kadhirvel, (Indian Journal of Extension Education, 2023)
The Hon’ble Prime Minister of India has been addressing the nation every month since 2014 on the emerging issues of national and international importance through his Mann Ki Baat programme in radio. The issues related to agriculture and allied sectors covered in the programme have attracted the attention of farmers as well as the change agencies. The importance of the Farmers' Producer Company (FPCs) and their role in strengthening the farmers’ income were highlighted in Mann Ki Baat. The present study was undertaken to assess the effect of the episodes on the farmers as well as the FPOs. An integrated approach of survey and case study method with ex-post-facto research design was followed. Using purposive sampling, 44 FPOs were selected from across the country covering 40 districts from 19 states for the study. The survey results showed that 98.50 per cent of the FPOs were formed during the PM’s Mann Ki Baat programme (2014-2023), FPOs had the highest shareholders of 4409 and paid-up capital of Rs. 1.31 crore. The business of FPOs covered almost all major crops, seed production of important crops, sale of agricultural inputs especially fertilizers and pesticides, custom hiring and value-added products. Successful cases of entrepreneurship development in FPOs were observed e.g., Puthari Farmers Producer Co Ltd., Kodagu, Karnataka operating at 10000 ha land of plantation crops with a turnover of Rs. 2.20 crore. Due to collective action, there was a reduction in the cost of cultivation by 20-25 per cent. FPOs’ feedback indicated that with Mann Ki Baat episodes, most of them became aware of the different policies and schemes. The FPOs are ensuring several benefits to member farmers like acquainting different government schemes, delivering inputs at doorsteps, reducing the cost of cultivation and so on. However, there is a need to strengthen FPOs through further support from government and allied departments. With awareness and increasing access to institutional resources through the enabling environment, being made by Mann Ki Baat, the employment opportunities and livelihood resilience of farmers will be improved